Measuring Soil Moisture in Real-Time: Arduino Uno Based Tool Innovation - Muhammad Akbar Syahbana Pane; Khairul Saleh (Ali Institute or Research and Publication, 2025)
Humidity measurement is vital across various sectors, such as agriculture, meteorology, industry, and households, where accurate monitoring ensures product quality, environmental stability, and process efficiency. Over time, humidity measurement technologies have evolved significantly, transitioning from basic evaporation-based methods to advanced electronic sensors like capacitive and resistive sensors, which offer real-time accuracy. Hygrometers and moisture meters are key devices in this field, with hygrometers measuring air humidity and moisture meters assessing water content in materials like soil, wood, and grains. Their integration with automation systems further enhances operational efficiency and simplifies environmental monitoring. Despite these advancements, challenges persist, including the need for higher accuracy, adaptability to diverse environments, and cost reduction. Research and development continue to tackle these issues, driving innovation toward more reliable, user-friendly, and affordable solutions. This article reviews the latest advancements in humidity measurement technologies, highlights the challenges faced, and explores future innovations that promise to enhance the accuracy and efficiency of these devices. Such progress is crucial for sustainability and improved performance in fields dependent on precise humidity data, ultimately supporting better decision-making and resource management.